A Content Analysis of English Textbook Related to Contextual Teaching and Learning - Syaiful Haque; Muhimatul Ifadah; Dodi Mulyadi (Universitas Muhammadiyah Semarang, 2018)
This research was aimed to investigate whether the English Textbook Contextual Teaching and Learning “Bahasa Inggris Sekolah Menengah Pertama” fulfilled the criteria of good textbook suggested by government and supporting the contextual teaching and learning. This research was designed in collaboration of descriptive qualitative and quantitative analysis. The object of this research was Textbook entitled “Bahasa Inggris Sekolah Menengah Pertama”. Library research and analysis were used to collect the data, while the instruments used were analysis sheet and interview. The result of this research showed that the textbook met the criteria of good textbook with the score for content fulfilment was 84.86%. The lowest achievement was in the criteria of cooperative fulfilment, which only achieved 28.18%. The researcher suggested that teacher could be more flexible in delivering the material of the textbook. For supplementing cooperative activity, teacher could arrange the activities that give students opportunity to collaborate in pairs.